Positive effect of incorporating Er0.4Bi1.6O3 on the performance and stability of La2NiO4+δ cathode - He, Zelong (2020)
Layered Ruddlesden-Popper La2NiO4+δ (LNO) is reported to possess excellent oxygen surface and bulk transport properties, but its application as the cathode of solid oxide fuel cells is restrained by the relatively poor electrocatalytic activity. Here, we report the incorporation of highly ion-conducting Er-stabilized Bi2O3 (ESB) into LNO and assemble the LNO-ESB composite cathode directly on zirconia electrolyte film using a facile electrochemical polarization approach. The results show the presence of ESB remarkably reduces the contact resistance at the electrode/electrolyte interface and enhances the electrocatalytic activity and cation stability of LNO. The cell with the LNO-ESB cathode generates a peak power density of 852 mW cm-2 at 750°C with reasonable operating stability over 200 h. This work demonstrates the feasibility of incorporating ESB to promote the layered nickelate cathodes for intermediate temperature solid oxide fuel cells.